El fútbol barrial como una forma de interacción comunicativa. :Caso del Club Imprenta Ideal en la Liga parroquial de Tumbaco - Díaz Salazar, Víctor Josue (2015)
This research aims to determine how the neighborhood football can be a space for interaction, leisure, play and unity among individuals, revealing the communicative, social and cultural practices of the club Printing Ideal Parish Tumbaco. To these will be discussed in three chapters. In the first chapter analyzes and contrasts the progress of societies with sport (football), also concepts as defined: sport, game, football to reach the differentiation between professional and neighborhood football, as with the passage of the years has been considered the first as a business crowd, while the second is the alternative to build through this sport a space for interaction. Later the main theories related to processes of interaction and communication studies, highlighting cultural, social, economic and political issues that have made this sport a cult in Latin American societies. Finally it will release the social, cultural and communicative practices carried out in the neighborhood football through interviews, statistics and analysis of the Club Printing Ideal to show that football can be a space for communicative interaction.